The Consequences of Interfaith Marriage Law on the Inheritance of Wives and Children Reviewed from the Compilation of Islamic Law - Handayani, Putri; Widodo, Ernu; Subekti , Subekti (Jurnal Indonesia Sosial Sains, 2025)
Indonesia’s multicultural and multi-religious society often leads to interfaith marriages, which present complex legal implications, particularly regarding the rights of spouses and children in matters of inheritance. Interfaith marriage raises significant legal questions under Islamic law, especially in terms of the status of heirs when religious differences exist between the deceased and the beneficiary. This study aims to examine the legal position of wives and children from interfaith marriages as heirs within the framework of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI). Employing a normative legal research method, this study analyzes statutory regulations, legal principles, and authoritative interpretations of Islamic inheritance law. The findings reveal that interfaith marriages give rise to legal consequences in three main areas: the legality of the marriage itself, the division of marital property, and the rights of children as descendants. According to KHI and prevailing Islamic jurisprudence, heirs who differ in religion from the deceased are not entitled to inheritance. However, the concept of mandatory will (wasiat wajibah) offers an alternative legal remedy, allowing non-Muslim heirs to receive a portion of the estate under certain conditions. This research implies the need for greater legal clarity and public awareness regarding inheritance rights in interfaith marriages to ensure justice and certainty for all parties involved.